2019
DOI: 10.1186/s42269-019-0089-7
|View full text |Cite
|
Sign up to set email alerts
|

Potential prophylactic effect of chemical chaperones for alleviation of endoplasmic reticulum stress in experimental diabetic cataract

Abstract: Background: Imbalance between protein synthesis and endoplasmic reticulum (ER) capacity to modify and fold proteins lead to the accumulation of unfolded proteins resulting in ER stress and apoptosis. Chaperones are major defense molecules assisting in protein folding, transport, and cellular signaling. ER stress plays a major role in the pathogenesis of diabetes mellitus (DM) and its complications, e.g., diabetic cataract. In the present investigation, the chemical chaperones 4-phenylbutyric acid (4-PBA), taur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…We also showed that CSE-induced RhoA activation was normalized by GSK2606414, a PERK inhibitor, and TUDCA. TUDCA has been known to function as not only a chemical chaperone but also an antioxidative agent in animal models of neurodegenerative disorders and ocular disorders 33 37 . Furthermore, TUDCA can be safely administered to humans and has been shown to have a pharmacological effect 38 41 .…”
Section: Discussionmentioning
confidence: 99%
“…We also showed that CSE-induced RhoA activation was normalized by GSK2606414, a PERK inhibitor, and TUDCA. TUDCA has been known to function as not only a chemical chaperone but also an antioxidative agent in animal models of neurodegenerative disorders and ocular disorders 33 37 . Furthermore, TUDCA can be safely administered to humans and has been shown to have a pharmacological effect 38 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Beneficial effects of TUDCA have also been suggested in studies of diabetic cataract [23] and diabetic retinopathy [100]. TUDCA was demonstrated to markedly retard the occurrence of cataract due to reduced ER stress and diminished oxidative stress [23].…”
Section: Tudca In Diabetes and Obesitymentioning
confidence: 94%
“…Type 2 diabetes is typically associated with normal insulin production, but lower insulin sensitivity of cells, which in consequence leads to elevated glucose levels in the blood [12,84]. An increasing number of reports from experimental and clinical studies also indicate a higher prevalence of cardiac damage [98], obesity [99], vision impairment [23,100], and nephropathy [101,102] in diabetic patients. According to a growing number of data, ER stress is a key contributor to the pathology of diabetes and is associated with pancreatic beta cell loss and insulin resistance [103,104].…”
Section: Tudca In Diabetes and Obesitymentioning
confidence: 99%
See 2 more Smart Citations